Name Tags and Net Tags: Investigating Username Construction as Identity Markers among Nigerian TikTok Creators - Mohammed Sani Ya'u; Mustapha Muhammad (Language, Technology, and Social Media, 2026)
In Nigeria’s active digital space, TikTok has become a popular platform where creators express their identities using carefully chosen usernames. This study investigates how Nigerian TikTok creators use usernames as identity markers, reflecting cultural, linguistic, and social affiliations in a multicultural context. Drawing on a manually compiled list of 200 top Nigerian TikTok influencers, ranked by follower count in April 2025, the research employs qualitative content analysis to examine username patterns. This aligns with the study’s objectives to identify linguistic and cultural elements, analyze usernames as identity markers, and infer influencing factors. Findings reveal that 15% of usernames reference Nigerian names or cultural figures, 2.5% incorporate national symbols like the Nigerian flag emoji, 25% include emojis or symbols, 40% use authenticity conventions such as “official” or “real”, and 20% reflect entertainment or trendy nicknames tied to content niches. These patterns highlight how creators blend cultural pride, linguistic creativity, and social engagement to navigate global digital spaces while celebrating Nigeria’s diverse heritage. The primary limitation of this study is the absence of survey data, meaning inferences about creators' motivations are based solely on content analysis and existing literature, rather than direct input from the creators themselves. This study uniquely addresses an important gap in research by specifically looking at how Nigerian TikTok creators intentionally create usernames as clear identity markers. It offers new insights into how digital identity is formed in non-Western settings, highlighting how cultural representation and language diversity interact online.